Yuri Lotman’s view of the cultural code - M. M. Pentsova (Vestnik MGIMO-Universiteta, 2013)
The article reveals Y. Lotman’s view of the cultural code as an explosion, which is opposed to a gradual movement. The stages of the explosion are depicted.